Analisis Validasi Soal Tes Hasil Belajar Pada Pelaksanaan Pembelajaran Bahasa Inggris - Otoluwa, Moon Hidayati; Ismail, Abdul Kadir (ELOQUENCE : Journal of Foreign Language, 2023)
Background: The teaching staff is not only responsible for the process of knowledge transactions but more than that, the teaching staff, in this case, lecturers, are also required to make assessment and measurement instruments to find out the extent to which students are able and able to master the English material in an evaluation process or rather a test. Purpose: To find out how the validity analysis of learning outcome tests made by English lecturers at the IAIN Sultan Amai Gorontalo Language Development Center Method: This research is evaluative research that evaluates question items using a quantitative approach. Results and Discussion: IAIN Sultan Amai Gorontalo lecturers tend to make learning outcome test questions in objective form based on practical courses' characteristics. With accurate tests, developing questions that can reveal students' applicative abilities, analysis, synthesis, and evaluation is more accessible than objective tests. In designing learning outcome test questions, not all lecturers (around 76%) make a grid of questions used as a reference for writing question items. Even though the grid is essential in writing good questions, in addition to writing questions, most lecturers use a combination of last year's questions and new ones. Making further questions related to the development of science and technology will be more meaningful. Conclusions and Implications: Not all lecturers of English courses at IAIN Sultan Amai Gorontalo have conducted a theoretical review regarding the quality of the questions that have been asked. However, one thing that is quite good and positive in the review that has been carried out by most lecturers, namely the most re-examined aspect, is the suitability of the question material with the competence of learning outcomes. There are still some weaknesses in several question sets, namely for objective tests. The aspect that is still weak is the non-uniformity of the short length of statements between answer choices and the separation of the main question page from the answer page. Another drawback to this form of the test is that there are still pictures accompanying the questions that are not clear.